Physics, Mechanics, Mathematics - Mahbod, Mohammad (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Dynamics features movement and stable means. Continuous Stable dynamics thus means continuous movement or motion. That is a moving object which enjoys continuous movement. For example, the electron continuous revolution round the nucleus, the revolution of the moon round the earth and that of the earth round the sun. In this formula, the continuous movement of the moving object round the origin of coordinates in space is studied. Regarding the importance of the angular speed calculation in most of applied sciences such as dynamic mechanics , aerospace , dynamic systems and lock of a relation established in this connection , the need is felt that in order to design and optimize dynamic systems , a reasonable relation should be presented . This paper tries to prove such a relation in the easiest possible way.